Gaea-Tima the gigantis. Vol. 03 - KENT (Manga artist) (Kodansha USA Publishing, 2025)
Sukuba native Yutaka, a kindhearted and brave young boy, is bullied at school and belittled by his dad at home. Determined to fight back, he challenges his classmates to a fight which doesn't quite go his way. Yutaka is the underdog, but he gets a surprise ally-a kaiju. This new sighting triggers more evacuations and military action. Everything Miyako and the FUNE team believe about GAEA-TIMA and kaiju behavior is about to be turned upside down.